Unveiling ammonia-induced cell death: a new frontier in clear cell renal cell carcinoma prognosis - Yu, Peize; Zhong, Qikai; Wang, Xinlei; Liu, Yifang; Liu, Qiang; Zhang, Yuqiang; Lu, Jiawei; Dong, Yang; Han, Cong-hui (Frontiers in Immunology, 2025)
BackgroundClear cell renal cell carcinoma (KIRC) is the most aggressive renal carcinoma subtype of renal carcinoma, characterized by high mortality, early metastasis, and resistance to treatment. Ammonia-induced cell death (AICD) has recently been identified as a novel metabolic mechanism influencing tumor progression, yet its prognostic implication and regulatory networks in KIRC remain underexplored.MethodsTranscriptomic and clinical information from the TCGA-KIRC cohort and the validation cohort (E-MTAB-1980) were analyzed. Differentially expressed AICD-related genes were identified through differential expression analysis, univariate Cox regression, and machine learning algorithms (LASSO, random forest, and CoxBoost). A prognostic risk model was developed via multivariate Cox regression. Spatial and single-cell transcriptomics were employed to characterize the immune microenvironment heterogeneity. Cell-based experiments were performed to investigate the potential involvement of ATP1A1 in KIRC. Molecular docking and pan-cancer analyses were conducted to identify therapeutic candidates and ATP1A1-related mechanisms.ResultsFive AICD-related genes (FOXM1, ANK3, ATP1A1, HADH, and PLG) were identified and selected to construct a risk score model. The model demonstrated high accuracy and was integrated into a nomogram for clinical application. High-risk (HR) patients exhibited immunosuppressive microenvironments, elevated tumor mutational burden (TMB), and genomic instability. In vitro functional assays confirmed that ATP1A1 knockdown significantly enhanced the proliferative, migratory, and invasive capabilities of renal carcinoma cells (A498 and 786-O), suggesting a suppressive role for ATP1A1 in malignant tumor progression. ATP1A1, a core gene, was associated with metabolic reprogramming and chemotherapy sensitivity across multiple cancers. Molecular docking revealed Emodinanthrone as a high-affinity ligand for ATP1A1 (−6.8 kcal/mol).ConclusionThis study identifies an AICD-associated gene signature as a robust prognostic tool for KIRC, revealing its interactions with immune evasion and genomic instability. ATP1A1 is proposed as a promising therapeutic target, with Emodinanthrone emerging as a novel drug candidate. These findings contribute to the advancement of personalized treatment strategies for KIRC patients.